What you will : gender, contract, and Shakespearean social space - Schwarz, Kathryn, 1966- (University of Pennsylvania Press, 2011)
Kathryn Schwarz considers sixteenth- and seventeenth-century narratives in which women willingly conform to social conventions. She argues that these acts of compliance construct a paradox of prescribed choice, which illuminates complex relationships between hierarchy and contract within heterosocial systems.